Village Fund Management and Community Economic Empowerment in a Remote Papua Highland Village - Topilus Sambom; Julius Ary Mollet; Risky Novan Ngutra (Goodwood Publishing, 2026)
Purpose: This study examines how Village Fund (Dana Desa) management in Helaksili Village, Yalimo Regency, Papua Mountains Province, contributes to community economic empowerment through physical infrastructure, community empowerment programs, and household income improvement. Methodology: A descriptive mixed-methods approach was employed, combining budget effectiveness analysis using the Kepmendagri No. 690.900.327/1996 ratio, a five-point Likert survey of 20 household respondents, and SWOT analysis. Data were obtained from the 2025 Village Budget (APBK) and official financial records using purposive sampling. Results: Budget realization reached 100%, indicating Very Effective performance. Village construction (35.03%) and governance (29.93%) received the largest allocations. Community perceptions were highest for infrastructure, moderate for empowerment programs, and lowest for household income improvement. Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis identified full budget realization as a strength, while high administrative expenditure and the absence of outcome-based indicators remained key weaknesses. Conclusions: Village Fund management was procedurally effective but substantively limited, indicating that budget absorption alone does not guarantee community welfare improvement.Limitations: The single-village setting, small sample (n = 20), and lack of baseline data limit generalizability and causal inference. Contributions: This study extends Village Fund research to Papua's remote highland context and introduces the proceduralsubstantive effectiveness gap as a framework for evaluating fiscal transfer programs and informing outcome-based rural development policies.